Links Between Obesity-Induced Brain Insulin Resistance, Brain Mitochondrial Dysfunction, and Dementia - Sripetchwandee, Jirapas; Chattipakorn, Nipon; Chattipakorn, Siriporn C. (Frontiers in Endocrinology, 2018)
It is widely recognized that obesity and associated metabolic changes are considered a risk factor to age-associated cognitive decline. Inflammation and increased oxidative stress in peripheral areas, following obesity, are patently the major contributory factors to the degree of the severity of brain insulin resistance as well as the progression of cognitive impairment in the obese condition. Numerous studies have demonstrated that the alterations in brain mitochondria, including both functional and morphological changes, occurred following obesity. Several studies also suggested that brain mitochondrial dysfunction may be one of underlying mechanism contributing to brain insulin resistance and cognitive impairment in the obese condition. Thus, this review aimed to comprehensively summarize and discuss the current evidence from various in vitro, in vivo and clinical studies that are associated with obesity, brain insulin resistance, brain mitochondrial dysfunction, and cognition. Contradictory findings and the mechanistic insights about the roles of obesity, brain insulin resistance, and brain mitochondrial dysfunction on cognition are also presented and discussed. In addition, the potential therapies for obese-insulin resistance are reported as the therapeutic strategies which exert the neuroprotective effects in the obese-insulin resistant condition.